Lung Transplantation in a Multidrug-Resistant Gram-Negative Acinetobacter Baumannii–Colonized Patient: A Case Report - Huenges, Katharina; Reinecke, Alexander; Bewig, Burkhard; Haneya, Assad; Cremer, Jochen (The Thoracic and Cardiovascular Surgeon Reports, 2016)
Colonization or infection with various pathogens is frequently found in patients listed for lung transplantation. We describe a case of a 50-year-old woman with α-1-antitrypsin deficiency, which was listed for double-lung transplantation, with multidrug-resistant gram-negative Acinetobacter baumannii (MRGN4-Ab) skin colonization. Transplantation was successfully performed. Colistin (Polymyxine E) was administered intravenously and through inhalation in the first month. MRGN4-Ab was still detectable in skin swabs without evidence of infection. After good recovery and clinical inapparence, the patient was discharged 2 months after transplantation.
Keywords: lung transplantation; α-1-antitrypsin deficiency; Multidrug-resistant Acinetobacter baumannii